2017
DOI: 10.1007/s00421-017-3544-x
|View full text |Cite
|
Sign up to set email alerts
|

Periodization effects during short-term resistance training with equated exercise variables in females

Abstract: Periodization is no adaptation trigger during short-term resistance training with equated exercise variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The data were nonnormally distributed and, therefore, log-transformed when analyzed and are presented as means Ϯ SD of raw data. no change (51,64,69,72) or only increases in FL (73) or PA (27,30,60). Based on previous studies (49,74), a greater FL increase induced by training is suggested to occur when training is performed at long MTU lengths due to a longer muscle stretch.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The data were nonnormally distributed and, therefore, log-transformed when analyzed and are presented as means Ϯ SD of raw data. no change (51,64,69,72) or only increases in FL (73) or PA (27,30,60). Based on previous studies (49,74), a greater FL increase induced by training is suggested to occur when training is performed at long MTU lengths due to a longer muscle stretch.…”
Section: Discussionmentioning
confidence: 89%
“…They found an increase in FL at the middle site when the training was performed at a short MTU length and at the distal site when the training was performed at a long MTU length, with no other FL adaptations. It is important to consider that the vastus lateralis and rectus femoris muscles act in synergy with other knee extensors, and thus adaptations may have been distributed across other knee extensors, as shown in other studies (13,26,60). To combat this limitation, we propose the tibialis anterior (TA) as a more suitable muscle to assess functional muscle architectural adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…In a strict sense, to periodize means "to establish periods for a historical, cultural or scientific process. " However, this term is commonly used to refer to the temporal organization of the training process, primarily the evolution of relative load and volume during the training cycle [83][84][85].…”
Section: Periodization Versus Programmingmentioning
confidence: 99%